Sistem Pendukung Keputusan Rekomendasi Pemberian Usaha Kredit Mikro (UKM) dengan Metode AHP-SAW (Study Kasus: PD. BPR Bojonegoro) - Siti Febrianti Ramadhani; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
BPR Bojonegoro is a Regional Owned Company under the auspices of Bojonegoro District. The following saving facilities provided by PD. BPR Bojonegoro namely Time Deposit, Savings which includes Saving Sight, Tapeda Saving, SWP Savings (Savings Borrower Savings) consisting of Employee Loans, Business Capital Loans. In the case of determination of credit in the Bank, (DSS) Decision Support System is needed in the decision of credit lending because it feels too risky for a credit given by the bank so that in the future does not cause problems that complicate the customer or harm the bank. In giving credit decisions used in PD. BPR Bojonegoro obtained from the surveyor survey, has not used the accurate method of selecting the creditor candidate. Therefore it is necessary method capable of supporting decision making more quickly, precise and accurate. In this research, the method used is AHP-SAW method. The AHP (Analitycal Hierarchy Process) method is chosen because of AHP's ability to handle problems with multiple criteria. These criteria are arranged hierarchically to solve major problems into sub-issues. The output of the AHP method is the weight of each criterion. This weight is used in SAW (Simple Additive Weighting) to determine the rank of the credit recipient. This research performs accuracy test with 89% result and usability testing test equal to 72,82%.